Establishment Of Tissue Culture Planting Materials Of Gac (Momordica Cochinchinensis) Using Improved Light Emitting Diodes (Leds) Technology And Silver Nitrate Treatment - Chew, Hong Lim (2021)
The Gac plant (Momordica cochinchinensis) of the cucurbitaceae family is native to the Southeast Asia region. The fruit has traditionally used as food and medicine due to their high levels of phytonutrients and antioxidants particularly beta-carotene and lycopene. M. cochinchinensis nodal explants used for the establishment of plant tissue culture system. The best plant growth regulator (PGR) for shoot regeneration in nodal segment explants of gac plant obtained by using semi-solid MS medium with 4mg/L BAP resulted an average of 9.2 shoots per explant and an average of 2.247 cm in length after 4 weeks. The best PGR for root induction for nodal segment explants of gac plant obtained by using semi-solid MS medium with 4mg/L IBA resulted an average of 13.2 roots per explant and 4.29cm in length after 4 weeks. After obtaining the optimum PGRs for the growth, gac nodal explants subjected with the treatment of various types of LED spectrums such as white (control), green, far-red, red, blue and purple [blue and red(1:1)] LEDs for duration of 4 weeks. Red LED spectrum displayed the most significant effect on shoot and root induction of gac explants. Explants under red illumination produced the highest average number of shoots which was 13.7 and an average of 2.193 cm in length.